Acute Low Dose of Trazodone Recovers Glutamate Release Efficiency and mGlu2/3 Autoreceptor Impairments in the Spinal Cord of Rats Suffering From Chronic Sciatic Ligation - Cisani, Francesca; Roggeri, Alessandra; Olivero, Guendalina; Garrone, Beatrice; Tongiani, Serena; Di Giorgio, Francesco Paolo; Pittaluga, Anna (Frontiers in Pharmacology, 2020)
We investigated whether chronic sciatic ligation modifies the glutamate release in spinal cord nerve endings (synaptosomes) as well as the expression and the function of presynaptic release-regulating mGlu2/3 autoreceptors and 5-HT2A heteroreceptors in these particles. Synaptosomes were from the spinal cord of animals suffering from the sciatic ligation that developed on day 6 post-surgery a significant decrease of the force inducing paw-withdrawal in the lesioned paw. The exocytosis of glutamate (quantified as release of preloaded [3H]D-aspartate, [3H]D-Asp) elicited by a mild depolarizing stimulus (15 mM KCl) was significantly increased in synaptosomes from injured rats when compared to controls (uninjured rats). The mGlu2/3 agonist LY379268 (1000 pM) significantly inhibited the 15 mM KCl-evoked [3H]D-Asp overflow from control synaptosomes, but not in terminals isolated from injured animals. Differently, a low concentration (10 nM) of (±) DOI, unable to modify the 15 mM KCl-evoked [3H]D-Asp overflow in control spinal cord synaptosomes, significantly reduced the glutamate exocytosis in nerve endings isolated from the injured rats. Acute oral trazodone (TZD, 0.3 mg/kg on day 7 post-surgery) efficiently recovered glutamate exocytosis as well as the efficiency of LY379268 in inhibiting this event in spinal cord synaptosomes from injured animals. The sciatic ligation significantly reduced the expression of mGlu2/3, but not of 5-HT2A, receptor proteins in spinal cord synaptosomal lysates. Acute TZD recovered this parameter. Our results support the use of 5-HT2A antagonists for restoring altered spinal cord glutamate plasticity in rats suffering from sciatic ligation.